Properties of transparent oxide thin films prepared by plasma deposition - Domaradzki, Jarosław; Borkowska, Agnieszka; Kaczmarek, Danuta; Prociów, Eugeniusz L. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this paper, thin films of TiO2 were deposited onto (100) oriented silicon and glass substrates using low pressure hot target reactive magnetron sputtering (LP HTRS) method. X-ray diffraction (XRD) and optical transmission measurements have been applied to study the influence of substrate type on the microstructure and optical properties of the prepared thin films, respectively. Thin films exhibit the TiO2-anatase crystalline state, which could be confirmed by the appearance of peaks of (101) orientation.
Optica Applicata, Vol. 35, 2005, nr 3, s. 425-430
Keywords: optyka; transparent thin film; sputtering process; titanium oxide; hot target